Implementation of Integrity Zone Development in Strengthening the Quality of Public Services at the Botanical Gardens Conservation Center Purwodadi - Indonesian Institute of Sciences - Khoiril Anam; Suryadi Suryadi; Hermawan Hermawan (Sekolah Pascasarjana Universitas Brawijaya, 2020)
The aim of this study to determine the implementation of PERMENPAN No. 10 of 2019 in the lever component of strengthening the quality of public services at the Botanical Gardens Conservation Center Purwodadi - Indonesian Institute of Sciences. With the target achieved, namely: improving the quality of public services, service units that obtain international standardization, public satisfaction index. In this study using qualitative methods, and qualitative data obtained through data collection techniques through interviews, study documentation, and observation. The data analysis technique is a qualitative model by Miles and Huberman. Penelitian implementation is based on four variables according to the theory of George C.E III , namely connection, assets, commitment, and bureaucratic arrangement. Based on the results of the study, results from satisfaction index society towards quality public services in 2019 scored very well with rat a-average satisfaction of 89,42. This is supported by Competency Enhancement, Public complaints services, Providing Complete and Clear Media Information, Public Service Innovations, Transparent procurement of goods and services. All of that proves that the WBK and WBBM predicates obtained are not just mere predicates, but need an increase in the form of external communication and the addition of Resources.